COVID-19 Related Psychological Distress, Fear and Coping: Identification of High-Risk Groups in Bangladesh - Rahman, Muhammad Aziz; Rahman, Shaila; Wazib, Amit; Arafat, S. M. Yasir; Chowdhury, Zulfia Zinat; Uddin, Bhuiyan Mohammad Mahtab; Rahman, Mufti Munsurar; Bahar Moni, Ahmed Suparno; Alif, Sheikh M.; Sultana, Farhana; Salehin, Masudus; Islam, Sheikh Mohammed Shariful; et al. (Frontiers in Psychiatry, 2021)
Background: The COVID-19 pandemic has imposed psychological distress and fear across the globe; however, factors associated with those issues or the ways people cope may vary by country or context. This study aimed to investigate the factors associated with psychological distress, fear, and coping strategies for people living in Bangladesh during the COVID-19 pandemic. Methods: A cross-sectional study conducted in August-September 2020 using online platforms in Bangladesh. People residing in Bangladesh, aged ≥18 years, who were proficient in English and able to respond to online questionnaire. The Kessler Psychological Distress Scale was used to assess the psychological stress. Level of fear was assessed using the Fear of COVID-19 Scale, and strategies to cope were assessed using the Brief Resilient Coping Scale. Results: Of the 962 participants, half of them were aged between 30-59 years. Higher levels of both psychological distress and fear were associated with being born in Bangladesh, having graduate education, perceived distress due to employment change, effect of COVID-19 on financial situation, having multiple comorbidities, and visiting a healthcare provider in the last four weeks. Furthermore higher psychological distress was associated with being a female (AOR 1.81, 95% CIs 1.33-2.47, p<0.001), being a frontline worker (1.50, 1.04-2.15, p<0.05), having pre-existing psychiatric problems (4.03, 1.19-13.7, p<0.05), being a smoker (2.02, 1.32-3.09, p<0.01), providing care to a known/suspected COVID-19 patient, having a recent overseas travel history and being in quarantine, self-isolation without COVID-19 or being COVID-19 positive, and having high levels of fear of COVID-19. A higher level of fear was associated with moderate to high levels of psychological distress. People with pre-existing mental health problems were less likely to be resilient (0.25, 0.11-0.54, p<0.01), whereas those with having an income were more likely to be resilient (1.46, 1.02-2.11, p<0.05). Conclusion: Effective interventions to support the vulnerable groups including improved access to mental health services are of utmost importance during the pandemic.